PS5:101 Nuclear antigen-reactive cd4+ t cells are expanded in active sle, correlate with disease activity, invade target organs such as the kidneys, and outnumber their regulatory counterparts. (21st March 2018) - Abdirama, D; Tesch, S; Griessbach, A-S; Scheffold, A; Radbruch, A; Stervbo, U; Babel, N; Burmester, G-R; Humrich, JY; Riemekasten, G; Enghard, P
Abstract : Background and objectives: Loss of tolerance towards nuclear antigens such as SmD1, RNP70, Histone, Ro, and La due to defective defective disposal of biological waste is characteristic of SLE. The question whether CD4 +T cells reactive to the aforementioned autoantigens are also implicated in SLE remains unclear. To study the role of autoreactive CD4 +T cells in SLE, we determined their frequency in healthy and diseased state, investigated their antigen specificity, characterised their cytokine production, interrogated their localization in the tissue, and analysed their homeostatic balance with autoreactive regulatory T cells (Treg). Materials and methods: We employed: T cell library to detect peripheral nuclear autoantigen-reactive CD4 +T cells, antigen-reactive T cell-enrichment to interrogate their cytokine production, generation of T cell clones and T cell lines to validate their specificity, TCR-beta analysis to predict their clonal occurence in blood and urine, urinary T cell library to detect and enumerate their frequencies in urine, CFSE-labelled urinary cells to detect and enumerate their frequencies in urine, and enrichment of CD137 +FoxP3+cells to investigate nuclear antigen-reactive Treg. Results: The frequency of autoreactive CD4 +T cells is greater in active SLE patients when compared with inactive SLE patients and healthy individuals, and it correlates with disease activity. Single-cell clones of autoreactive CD4 +T cells confirmed their antigen specificity. Autoreactive CD4 +T cells produced pro-inflammatory cytokines such as IFN-gamma, IL-17, and IL-10, where the production of IFN-gamma correlates with disease activity. The accumulation of these cells was detected in urine of active SLE patients with lupus nephritis when compared with their number in the periphery. The ratio of autoreactive effector T cells against autoreactive Treg is higher in active SLE patients when compared with inactive SLE patients and healthy individuals, and it correlates with disease activity. Conclusions: Our data demonstrate that higher frequency of autoreactive CD4 +T cells in the periphery could contribute to disease progression of SLE. Accumulation of these cells in urine suggested their possible role in mediating local tissue inflammation. Homeostatic imbalance between autoreactive effector T cells and Treg indicated an insufficient regulatory mechanism to control autoimmunity at antigen-specific level.